Die Moderne Benadering tot Infeksiesiektes - O.W. Prozesky (AOSIS, 1978)
The combat against infectious diseases stands at the moment on the threshold of yet another revolution, similar to the previous one which was brought about by antibiotic therapy. This new revolution is not attributed to a remedy or group of new remedies but rather to a new conviction, a realisation, that prevention is immeasurably better than treatment, and that community health, in the broadest sense, is immeasurably more effective than the single-patient approach of the past.